Pengaruh Terapi Pijat Refleksi terhadap Penurunan Tekanan Darah pada Lanjut Usia dengan Hipertensi - Levi Tina Sari; Nevy Norma Renityas; Wahyu Wibisono (Journal of Ners and Midwifery, 2014)
Elderly in the age of 60 or above is a natural process that can not be avoided where the life of man as a human being is limited by a rule of nature. As a result of the aging process, the blood vessels become stiff and affect the left ventricular wall reduce its elasticity, resulting in a progressive increase of blood pressure. The treatment of hypertension in addition to pharmacological therapy could also use non-pharmacological therapies such as reflexology massage. Â Method: The research design used in this study was pre-experimental using one group pretest-posttest approach. In this research, the researchers measured blood pressure before and after the treatment (reflexology massage). The sample of this study was 20 respondents using purposive sampling. This research used statistical t-test analysis test, because it had a scale ratio data. Result : The result of t-test showed that p <0.0001, means that there was significantly different result before and after treatment with reflexology massage on the feet with a medium timber. Discussion : It is expected that people with hypertension do the feet reflexology massage in order to taking medication because can lower systolic blood pressure.